Analysis of Mathematical Literacy Processes in High School Students - Tri Rahmah Hayati; Kamid Kamid (International Journal of Trends in Mathematics Education Research, 2019)
The results of the Programme for International Students Assessment (PISA) survey published by the Organization for Economic Cooperation and Development (OECD) show that Indonesia is still a country with low mathematical literacy skills. The ability of mathematical literacy is closely related to interpreting contextual problems into mathematical language. In modern times like today, what is needed is not only mathematics as arithmetic, but also mathematical literacy is needed related to mathematical reasoning and problem solving. The government has included contextual aspects of the curriculum applied in schools. However, in reality many schools still do not have contextual abilities that are in line with the still low literacy abilities of students in Indonesia. The purpose of this study is to describe the mathematical literacy process in senior high schools which in this study were students with majoring in science and students with majoring in social studies. This type of research is descriptive qualitative research. The research subjects were grade X students majoring in science and majoring in social studies. The instruments used in this study were the authors themselves, math literacy questions sheets, and interview guidelines. The results showed that the mathematics literacy process of high school students obtained was both students with majoring in Natural Sciences and students with majoring in Social Sciences are 1) The social science students have been able to reasoning and planning to solve the problem well, even though there still mistakes. The natural science students well in calculation and use formula. However, the natural science students are unable not to argue mathematically and express opinions. 2) the social science students are not good at reasoning and planning to solve the problem, however well in express what students thought verbally. For diagrams translate and solve to math language, the students from social science still difficult. Use of formula in natural science students still not right.